Developing of Android Based Educational Games as a Supplementary Media For Vocabulary of Junior High School Students - Pantrisia Surtika Sari; Widiarini Widiarini; Siti Rofi'ah; Istina Atul Makrifah (Journal of Development Research, 2022)
The problem in learning English is almost all students have difficulty in learning vocabulary and the students lack of mastery of English vocabulary, another problem is that students' interest in learning vocabulary is very low because they think it is very difficult to memorize it. In addition, teachers do not use media to help the vocabulary learning process. So, the students need media to help learn vocabulary. The aim of this study is to develop the android based educational games and to know the result of develop the android based educational games. This type of study is Research and Development (R&D) used the Borg and Gall procedure which uses 6 stages out of 10 stages of development. There are need analysis, product design, product validation, product revision, product testing, and revise the product. The subject of the research is seventh grade students in SMPI Hasanuddin Kesamben. The feasibility of the media based on the results of the percentage of expert validation, namely: 92% media experts with Valid/Very Decent categories, material experts 81.25% with Valid/Very Decent categories. Furthermore, the results of student satisfaction were 89% with the product category "Valid / Very Decent". Based on these results, it can be concluded that the Android-based educational game media for vocabulary is very interesting to use as a supplementary media.